The Effect of LSLC - Based Problem Based Learning Model on Student Learning Outcomes on Atomic Structure Material – Nanomaterials for Class X SMA Penggerak - Istiqori, Hikmah; Fitriza, Zonalia; Haowraida , Haowraida (Journal of Educational Sciences, 2022)
A proper learning process can improve student learning outcomes. Therefore, appropriate learning models and systems are needed. The LSLC-based Problem Based Learning (PBL) model can be used as a solution. This study aims to determine the effect of the LSLC-based PBL model on learning outcomes in the aspects of knowledge, skills, and attitudes of students on the atomic structure-nanomaterial. This study is a quasi experimental with a randomized posttest only control group design.Which was held to two classes of class X SMAN 9 Padang. The results show that the learning outcomes were normally distributed and had a homogeneous variance. Therefor, the t-test was done to test the hypothesis which the demonstrated Tcritical> Ttable. For those three kinds of learning outcomes, which were knowledge learning outcomes (1.9595 > 1.669); skill learning outcomes (1.9752 > 1.8124); attitude learning outcomes (2.4206 > 1.8124). The result prove that of the application of the LSLC-based PBL model on the atomic structure-nanomaterial topic has a significant effect on improving knowledge, skills, and attitude.